2016 HIGHLY CITED RESEARCHERS – THREE OUT OF SIX FROM MALAYSIA ARE FROM USM - MPRC, Pusat Media & Perhubungan Awam (2017)
Three out of six researchers from Malaysia who are listed in the 2016 World’s Highly Cited Researchers, released recently by Clarivate Analytics, come from Universiti Sains Malaysia (USM).